Multiscale Meshfree Analysis of the Effects of Thermal Treatments on Deformability of Red Blood Cell Membrane - Adesola Ademiloye (2016 IEEE 16th International Conference on Bioinformatics and Bioengineering (BIBE), 2016)
From temperature conditions in blood storage units to those observed in patients with severe thermal burns, it is obvious that the human blood cells are subjected to various temperature ranges and conditions during their lifespan. It is also known that temperature affects the ability of blood cell to transverse thin microcapillaries, although the extent remains unknown. In this study, we employed a three-dimensional (3D) nonlinear multiscale meshfree approach to investigate the effects of freezing and heating temperatures on the deformability of the human red blood cell (RBC). The optical tweezers experiment was numerically simulated in order to quantify the deformability of red blood cells as a function of the relationship between its deformed axial and transverse diameter. We observe that the deformability of red blood cell membrane decreases as temperature increases. It is concluded that increase in temperature leads to increase in membrane rigidity and decrease in overall membrane deformability, which may be due to the denaturation of RBC membrane underlying cytoskeleton protein.